2021
DOI: 10.1038/s41598-021-81812-5
|View full text |Cite
|
Sign up to set email alerts
|

Residual and ecological risk assessment of heavy metals in fly ash from co-combustion of excess sludge and coal

Abstract: Co-combustion of municipal excess sludge (ES) and coal provides an alternative method for disposing ES. The present study aims to investigate the residual and ecological risk of heavy metals in fly ash from co-combustion of ES and coal. The total concentration and speciation distribution of heavy metals, characterization of SEM, EDX, XRD and leaching test were carried out to assess the fly ash in this study. The results showed that the total concentrations of Cu, Zn and Mn were higher than others in fly ash, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…As can be seen from Figure 6B, the leaching of heavy metals generally showed an upward trend with a decrease in particle size, which is consistent with the results of Zhou et al (2015a) and Tang et al (2021). Cd, Cr, Cu, and Ni leaching increased with decreasing particle size, with no significant differences observed among these metals.…”
Section: Effect Of Particle Size On Fly Ash Heavy-metal Leachingsupporting
confidence: 86%
See 2 more Smart Citations
“…As can be seen from Figure 6B, the leaching of heavy metals generally showed an upward trend with a decrease in particle size, which is consistent with the results of Zhou et al (2015a) and Tang et al (2021). Cd, Cr, Cu, and Ni leaching increased with decreasing particle size, with no significant differences observed among these metals.…”
Section: Effect Of Particle Size On Fly Ash Heavy-metal Leachingsupporting
confidence: 86%
“…Zhou et al (2015a) investigated the content and morphology of heavy metals in fly ash composed of different particle sizes, finding that volatile metals (such as Zn, Pb, Cu, and Cd) tended to be more abundant in finer particles, resulting in a higher risk to human and environmental health. Furthermore, Tang et al (2021) also found that heavy metals are more concentrated in finer particulate matter, with the potential ecological risk increasing as the particle size of fly ash decreases. Risk assessment is an important way to evaluate the environmental safety of heavy-metal risks.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The ecological risk index (RI) was applied to assess the risk based on heavy metal leaching from sludge-based biochar application based on eqn (1) and (2): 15,16 RI = ∑ E i where E i is a single potential ecological risk factor for each heavy metal including Cd, As, Cu, Ni, Zn and Pb, respectively; T i is the toxic factor of each heavy metal and the values are 30 (Cd), 10 (As), 5 (Cu), 5 (Ni), 1 (Zn) and 5 (Pb), respectively; 15,17 C i and C 0 are the measured value and control reference value for each heavy metal, respectively. The classification of risk levels based on E i and RI is shown in Table S1 of the ESI †…”
Section: Methodsmentioning
confidence: 99%
“…The ecological risk index (RI) was applied to assess the risk based on heavy metal leaching from sludge-based biochar application based on eqn (1) and (2): 15,16…”
Section: Leaching Test and Ecological Risk Assessmentmentioning
confidence: 99%